Integrasi Nilai Pendidikan Islam dalam Mendukung Pencapaian Sustainable Development Goals 2030 - Manda Apta Firanti; Dinda Pratiwi; Gladicya Amanda Br. Purba; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the integration of Islamic education values in supporting the achievement of the Sustainable Development Goals (SDGs) 2030. The background of this research is rooted in the increasing global demand for education systems that not only emphasize cognitive competence but also foster moral integrity, social responsibility, and environmental awareness. Islamic education, with its foundational values such as tawhid (divine consciousness), adl (justice), amanah (responsibility), and mizan (balance), offers a holistic framework that aligns with the principles of sustainable development. The objective of this research is to analyze how Islamic educational values can be conceptually and operationally integrated into educational practices to contribute to the SDGs agenda. This study employs a qualitative approach using library research as the primary method, collecting and analyzing relevant academic literature published in recent years. The findings indicate that the integration of Islamic values through contextual learning, reflective discussions, character-building activities, and social engagement initiatives can enhance students’ awareness of global issues, empathy, inclusivity, and ecological responsibility. Although challenges remain in curriculum standardization and character assessment mechanisms, the study concludes that Islamic education has strong potential to function as a transformative educational model. The implications of this research suggest the need for curriculum development, teacher capacity building, and institutional commitment to ensure that Islamic education meaningfully contributes to sustainable global development.